SÓZ OYIN QOSIQLARI HÁM BALALAR FOLKLORI - Biysenbaev, Q. (SCIENCE and SOCIETY, 2022)
In the article, the genesis, genre features, system of images, linvopoetics of "Word game songs" belonging to Karakalpak folklore, including children’s folklore, as an independent genre, are emphasized.